Formulation of stress concentration factors for concrete-filled steel tubular (CFST) T-joints under axial force in the brace. (1st September 2018) - Zheng, Jian; Nakamura, Shozo; Ge, Yajing; Chen, Kangming; Wu, Qingxiong
Highlights: Hot spot stress (HSS) of CFST T-joint under axial force in the brace was studied. Stress concentration factors (SCFs) were used to represent HSS. Validity of developed FE models was shown by the comparison with experiments. Influence of geometric parameters on SCFs was numerically examined. Formulae to estimate the SCFs were proposed and their validity was revealed. Abstract: CFST T-joints consisting of a concrete-filled circular chord and a circular hollow section brace have been used in CFST trussed arch bridges. The stress concentration factors (SCFs) of CFST T-joints have been found to be much lower than those of circular hollow section (CHS) T-joints in the existing researches. At present, no parametric formulae have been proposed for SCFs determination for fatigue design of CFST T-joints. In this study, three-dimensional finite element (FE) models of the existing experiments for CFST T-joints were developed to determine the SCFs distribution at the chord-brace intersection under axial force in the brace. After confirming the validity of the FE models by the comparison of calculated SCFs with existing experimental results, they were provided for the parametric analysis to reveal the influence of four non-dimensional parameters, i.e. diameter ratio ( β ), diameter to thickness ratio of chord (2 γ ), thickness ratio ( τ ) and relative chord length ( α ), on SCFs of CFST T-joints. In total, 212 FE models with different parameters were analyzed under tensile and compressive axial forces. Based on the results of parametric analysis, a series of parametric formulae to calculate the SCFs was proposed for CFST T-joints referring to those for CHS T-joints. The SCFs determined by the formulae showed good agreements with FE analysis results.